Job-Embedded Learning (JEL) and Monitoring and Evaluation Levelling (MEL): An Educator’s Aftermaths to Learning and Development Intervention (LDI) - Palanas, Victorina (JPAIR Institutional Research, 2020)
Teachers play a crucial role in improving the quality of the teaching and learning process. Hence, enhancing teacher quality ranks foremost in the many educational reform efforts toward quality education. (PPST, 2017). This study aims to improve the teaching-learning process as well as to increase the Mean Percentage Score (MPS) in all learning areas through Job-Embedded Learning (JEL) and Monitoring and Evaluation Levelling (MEL). Mixed-Method Research Design was used to continually ensure the conduct of open-ended techniques, which contributed to the successful implementation of Learning and Development Intervention (LDI). Data was collected and interpreted using graphical representations and Pareto Analysis. The contributing factors that help LDI successful were: Participants were given the opportunity to reinvent usual classroom routines suited to the current situation, and appropriate strategies were utilized according to the learners’ needs along with the available materials and equipment in the school. This structured JEL process requires that professionals should (a) plan to continue learning while on the job; (b) integrate their new learning with normal work activities; (c) constantly reflect upon and evaluate their work practice; (d) generate new insights and learning based on their reflections; and (e) share experiences and develop new insights with others. Improvement of work performance based on the result of the entire learning process.